THE IMPORTANCE OF THE NAQSHBANDIYA-MUJADDIDIYA DOCTRINE IN SHAPING THE SPIRITUALITY OF YOUTH IN THE CONTEXT OF GLOBALIZATION - Mirzaeva Feruzakhon; Sidikjonova Dilnozakhon (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the issues of shaping the spirituality of youth in the context of globalization and analyzes the spiritual and educational significance of the Naqshbandiya-Mujaddidiya doctrine in this process. The study explores the historical foundations of the Mujaddidiya branch of the Naqshbandiya order, its educational traditions, and its moral-philosophical principles. Based on historical and scholarly sources, the article highlights the importance of such concepts as knowledge and enlightenment, moral purification, self-discipline, social responsibility, tolerance, and teacher-disciple traditions in the spiritual upbringing of modern youth. The paper also discusses the role of Sufi teachings in protecting young people from spiritual threats, and the negative consequences of mass culture in the era of globalization.